Personification in Nursery Rhymes: A Semantic Study - Rafidah Nur Fauziah (Jurnal Sosial Teknologi, 2026)
The transformation of digital media consumption in early childhood has significantly changed patterns of language exposure and early literacy practices. In the midst of increasing children's access to global digital content, children's songs (nursery rhymes) in English that are disseminated through platforms such as YouTube and the Cocomelon Nursery Rhymes channel have become pedagogical artifacts that have a wide influence. This research aims to (1) identify types of personification and (2) analyze their communicative purpose in English children's songs circulating digitally. The research used a qualitative descriptive design with an interpretive semantic analysis approach. The data is in the form of lyrics from 20 children's songs in English which were selected purposively based on the criteria of an early age audience and potential figurative language content. The unit of analysis is the clause or lyric line that attributes human traits to non-human entities. The classification of personification types refers to Dodson's (2008) typology: general, representative, and casual personification. The research results showed that there were 52 occurrences of personification, with the dominance of general personification at 40 data (77%) and representative personification at 12 data (23%), with no casual personification found. These findings confirm that personification in digital nursery rhymes is not just a stylistic ornament, but rather a systematic semantic strategy to support cognitive accessibility and pedagogical orientation in early childhood discourse. This research contributes to strengthening the theoretical framework of figurative language analysis in the children's digital media ecosystem.